2020
DOI: 10.1007/s10450-020-00259-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-porous organic crystals and their interaction with guest molecules from the gas phase

Abstract: Some organic molecules encapsulate solvents upon crystallization. One class of compounds that shows a high propensity to form such crystalline solvates are tetraaryladamantanes (TAAs). Recently, tetrakis(dialkoxyphenyl)-adamantanes have been shown to encapsulate a wide range of guest molecules in their crystals, and to stabilize the guest molecules against undesired reactions. The term ‘encapsulating organic crystals’ (EnOCs) has been coined for these species. In this work, we studied the behavior of three TAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Some tetraaryladamantane ethers have attracted inte­rest because of their ability to include other molecules in their crystalline lattice. 24 25 26 27 28 29 30 31 32 Building on earlier work on diaryladamantanes 17 we recently showed that 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyadamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro) are able to act as crystalline hosts for liquid compounds. This property makes them useful as crystalline coats for hazardous or reactive compounds, 30 or reversible uptake of volatile organic compounds from the gas phase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some tetraaryladamantane ethers have attracted inte­rest because of their ability to include other molecules in their crystalline lattice. 24 25 26 27 28 29 30 31 32 Building on earlier work on diaryladamantanes 17 we recently showed that 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyadamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro) are able to act as crystalline hosts for liquid compounds. This property makes them useful as crystalline coats for hazardous or reactive compounds, 30 or reversible uptake of volatile organic compounds from the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…This property makes them useful as crystalline coats for hazardous or reactive compounds, 30 or reversible uptake of volatile organic compounds from the gas phase. 31 Further, either of these TAAs can be used as crystallization chaperones to determine the absolute configuration of small molecules that are liquids at room temperature. 32 The tetraaryladamantanes mentioned above can be synthesized by a route adapted from the work of Stetter, [19][20][21][22] starting with four-fold bromination of adamantane in the presence of a strong Lewis acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered organic molecular crystals are steadily gaining attention in the adsorption field, where conventionally nanoporous materials are playing a leading role. [1] Compared to COFs and MOFs, which commonly tend to contain pores in their crystal structures [2][3][4][5][6][7] direct assembly of discrete organic molecules giving rise to porous structures is challenging. Generally, they tend to pack efficiently to maximize attractive intermolec-ular contacts and minimize voids in the crystal lattice, giving rise to stable assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Engineered organic molecular crystals are steadily gaining attention in the adsorption field, where conventionally nanoporous materials are playing a leading role [1] . Compared to COFs and MOFs, which commonly tend to contain pores in their crystal structures [2–7] direct assembly of discrete organic molecules giving rise to porous structures is challenging.…”
Section: Introductionmentioning
confidence: 99%